Simulation study on the trajectory planning of table tennis robot arm by applying polynomial interpolation algorithm - Qiang, X.; Wen, W. (Journal of Physics: Conference Series, 2023)
Abstract: As the table tennis robotic arm is operated, it is easy to have problems such as discontinuity and instability, which lead to a decrease in work efficiency and thus increase the maintenance cost of the machine. Therefore, to improve the stability of the robotic arm, the study constructs the relationship model of the robotic arm linkage of the table tennis robotic arm and solves such difficulties by using a 4-5-4 polynomial interpolation algorithm. The experimental results show that, compared with the traditional 3-5-3 polynomial interpolation algorithm, the 4-5-4 polynomial interpolation is used to achieve continuous and smooth changes of angular displacement, angular velocity, angular acceleration, and torque of the robot, and there is no abrupt change. The 4-5-4 polynomial interpolation algorithm is used to achieve the stability of the robot and smooth operation of the robot arm.